The influence of Pb vacancies on the properties of PZT-type ceramic transducers - Z. SUROWIAK; L. KOZIELSKI; B. WODECKA-DUŚ; E.G. FESENKO; O.N. RAZUMOVSKAYA; L.A. REZNICHENKO; I.N. ZAKHARCHENKO (Archives of Acoustics, 2000)
This article is dedicated to prof. J. Ranachowski